An Analysis of Patients That Underwent Computed Tomography Pulmonary Angiography with the Prediagnosis of Pulmonary Embolism in the Emergency Department - Engin Ozakin; Filiz Baloglu Kaya; Nurdan Acar; Arif Alper Cevik (The Scientific World Journal)
Introduction. The purpose of this study is to analyze the frequency of other diagnoses and findings in patients that were diagnosed with or not diagnosed with PE following the CTPA in the ED and to analyze the relationship between diagnosis and D-dimer. Instrument and Method. This study involves all patients that presented to the ED that underwent CTPA with the prediagnosis of PE. The items considered in this study were their reason for presenting to the ED and pretest clinical risks for PE, D-dimer, and CTPA results. Findings. Of the 696 cases, the most common cause was shortness of breath (59.3%). The CTPA showed that 145 (20.83%) patients were suffering from PE. Among the remaining cases, 464 (66.66%) patients had pathological findings other than PE and 87 (12.5%) patients were reported as normal. The most common pathological results other than PE found in CTPA were atelectasis in 244 (39.9%) and ground glass in 165 (23.7%), as well as nonpulmonary results in 70 (10.05%) patients. The differences in D-dimer results of patients diagnosed with PE, patients diagnosed with another pathology, and patients with normal CTPA results were statistically significant (P<0.001). Conclusion. CTPA scanning, performed on the basis of assessment scoring, helps in discovering other fatal pathologies in addition to PE.